Typical agramaticalized constructions as actualized mono- and polysynonymic transforms of virtual primary syntagmata and propositions (on the material of modern french fiction) - Anastasia Lepetiukha (Когниция, коммуникация, дискурс, 2023)
In this article, mono- and polysynonymic typical agrammaticalized constructions are defined as virtual transforms of primary syntagmata and propositions, actualized in the form of reduced, extended, and quantitatively equacomponential preferential options, in which expressivity prevails over expression. The aim of this research was to suggest a typology and to determine the degree of co(n)textual pertinence of typical agrammaticalized mono- and polysynonymic transforms in modern French fiction. To reach this aim I used the procedure of inverse reconstruction (discourse → language) of the primary structure of the analyzed types of mono- and polysynonymic agrammaticalized discourse innovations. The method of systematization made it possible to build a typology of common agrammaticalized synonymic preferential options. An “alternative” linguistic experiment, i.e., an artificial substitution by the recipient of a certain syntagm or proposition of the analyzed discourse fragment by a synonymic syntagm or proposition, helped to determine the degree of co(n)textual pertinence of the primary structure and secondary synonymic transforms. As a result, the types of mono- and polysynonymic typical agrammaticalized constructions were distinguished, the primary structure and members of virtual synonymic series were inversely reconstructed, and the co(n)textual pertinence of the constructions under analysis was justified by means of the “alternative” linguistic experiment. I claim, that in the French fiction of the 20th ‒ 21st centuries, the most frequent elements are mono- and polysynonymic typical agrammaticalized mono- and polypredicative utterances, extended by the interrogative or relative pronoun que, the personal pronoun il (and its colloquial analogues), quantitatively equacomponential preferential options containing the pronominal component que, and elliptical constructions with final suppression of complement after prepositions avec, sans, pour, contre, parmi, comme. I also claim, that the main reason for actualizing typical agrammaticalized constructions is to emphatically focalize new co(n)textual referents, stylistically nuance the intra- and / or interphrasal co(n)text, syntactically simplify complex structures, or prevent the re-actualization of referents previously introduced to the pre- or post-text.